Effect Of Thermal Energy On The Filling Time Of Composite Encapsulant Underfilling Process With Various Filler Loading Of Nano Silica Filler Particles - Zulkurnain, Amru (Universiti Sains Malaysia, 2018)
The advance composite encapsulant with reinforce filler particle in the epoxy resin is a revolutionary advancement in the effort to improve the reliability of the electronic device. Many researches have been shown that by increase the amount of the filler particles in the composite encapsulant, the reliability and sustainability of the integrated circuit (IC) is improved. The introduction of higher amount of filler particles in the encapsulant in turn increasing the filling time of the underfilling process significantly. It has been found that the higher filler loading causing the encapsulant to become more viscous. In this research, straight forward solution to this is by incorporating additional energy during the underfilling process. In this research, simulation and experimental analysis is conducted to study the effect of thermal energy to the filling time of composite underfilling time at different filler loading. For simulation, finite volume method (FVM) based numerical solver using discrete phase model (DPM). From simulation and experimental results, it is proven that the thermal energy is able to reduce the filling time of the underfilling process between difference filler loading by average of 5%.